OUR MOTHERS’COURAGE SILENCED ALL GUNS: WOMEN AND CONFLICT IN THE NIGER DELTA - Ibeanu, O (University of Nigeria Journal of Political Economy, 2022)
Pacification of the Niger Delta seems to be a refrain of successive governments in Nigeria since the 1990s. Obviously,’ this is in response to years of local disaffection against multinational (Iii companies and government over poor social conditions and environmental degradation. A decade of violence led to the death and displacement of hundreds of thousands of people, destruction of livelihoods and decimation of the natural environment. In many communities in the Niger Delta. there is a widespread feeling that much has not changed with the new democratic government regarding state repression, as the military invasion and killings in the Ijaw town of 0di in November 1999 shows. In these conflicts, women suffered tremendously. Yet, it is wrong to assume, as it is widely done, that women are just passive victims of the conflicts and mere auxiliaries in the struggles of their communities for justice. While it is true that male populations are major targets of state violence, it is perhaps as true that the played by women in social provisioning for families and communities "and direct participation in the struggles helped to determine the course and outcomes of the conflicts. That notwithstanding, this role has not received the attention it deserves: This paper analyses the tire impact of prolonged conflict and state repression on Ogoni and Ijaw women. It analyses the various dimensions of abuses against women in the course of the conflicts, support networks for women, as well as how conflict experiences are changing the social position of women in these communities.